A Modern Course in the Quantum Theory of Solids. - Han, Fuxiang (World Scientific Publishing Company, 2012)
This book contains advanced subjects in solid state physics with emphasis on the theoretical exposition of various physical phenomena in solids using quantum theory, hence entitled "A modern course in the quantum theory of solids". The use of the adjective "modern" in the title is to reflect the fact that some of the new developments in condensed matter physics have been included in the book. The new developments contained in the book are mainly in experimental methods (inelastic neutron scattering and photoemission spectroscopy), in magnetic properties of solids (the itinerant magnetism, the.